ENHANCING POWER QUALITY IN DC SYSTEMS WITH UPFC-BASED MULTILEVEL CASCADE CONVERTER (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Mixture Although renewable energy is a good substitute for conventional energy, connecting it to the grid can provide new difficulties. Similarly, for wind turbines to keep the grid stable and reliable, they need to provide high-quality electricity. To reduce the harmful environmental effects of conventional energy generation, more wind turbines are being connected to the electrical grid. Understanding how disturbances impact the quality of the energy is important in order to connect a wind turbine to the grid. The voltage and frequency must be as stable as feasible. This stability may be obtained using FACTS devices. Inverters that are either voltage-source or current-source have been used recently to reduce oscillation in the power supply. Moreover, several of them are used to improve the transient and dynamic stability of wind power generating systems (WPGS). When a wind turbine is linked to the grid, it produces electrical switching behaviour, voltage sag and swell, flashing and harmonic emissions, and active and reactive energy. A three-phase grid-linked wind-driven induction generator's reactive power need may be adjusted in a number of methods, such as by applying instantaneous pq theory and UPQC to adjust for harmonics produced by a non-linear load connected to the PCC. MATLAB/SIMULINK is used to simulate the FACTS Device UPQC control mechanism in order to improve power quality.